2017
DOI: 10.1103/physrevlett.119.237202
|View full text |Cite
|
Sign up to set email alerts
|

Switching Molecular Conformation with the Torque on a Single Magnetic Moment

Abstract: For the endohedral fullerene molecule HoLu_{2}N@C_{80}, it is shown that the endohedral HoLu_{2}N unit may be oriented in a magnetic field. The Ho magnetic moment is fixed in the strong ligand field and aligns along the holmium-nitrogen axis. The torque of a magnetic field on the Ho magnetic moment leads to a hopping bias of the endohedral unit inclining to an orientation parallel to the externally applied field. This endohedral cluster distribution remains frozen below the onset of thermally induced rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…2(c) and the extracted moments in Table 1 reveals a 22% larger maximum XMCD signal at the M 5 -edge and a 10% larger magnetic moment from the peapod sample, consistent with a partial ordering inside the nanotubes. It has been demonstrated that the torque exerted on the anisotropic Ho 3+ moment in HoLu 2 N@C 80 from an external magnetic field can lead to a thermally activated endohedral hopping motion that tends to align the cluster parallel to the field above a freezing temperature T F ~ 55 K. 39 In the present case, the system was cooled from room temperature to 2 K in zero field, and it is not expected that the applied field influences the partial ordering along the tubes. To understand the origin of the partial ordering we turn to ab initio calculations.…”
Section: Resultsmentioning
confidence: 99%
“…2(c) and the extracted moments in Table 1 reveals a 22% larger maximum XMCD signal at the M 5 -edge and a 10% larger magnetic moment from the peapod sample, consistent with a partial ordering inside the nanotubes. It has been demonstrated that the torque exerted on the anisotropic Ho 3+ moment in HoLu 2 N@C 80 from an external magnetic field can lead to a thermally activated endohedral hopping motion that tends to align the cluster parallel to the field above a freezing temperature T F ~ 55 K. 39 In the present case, the system was cooled from room temperature to 2 K in zero field, and it is not expected that the applied field influences the partial ordering along the tubes. To understand the origin of the partial ordering we turn to ab initio calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic anisotropy is high and other J z states may be neglected since they have energies that are much higher than the thermal energies in the present experiments [21]. Below 50 K, the molecule orientation is frozen, and the ground states of the individual molecules are determined by the orientation of the external magnetic field with respect to that of the magnetic moments on the two Tb atoms [22,23]. For a given molecule this yields 2 2 possible ground state configurations that split into two time reversal symmetric doublets spanning the Hilbert space [10].…”
mentioning
confidence: 85%
“…the magnetic moments are not aligned to the external field but to the molecular coordinates that determine the anisotropy axes. In zero field cooled powder samples there is no preferential molecular orientation and the distribution of the Tb-N axes is isotropic [23]. In Figure 1(c) the energies of an ensemble of isotropically distributed molecules in different external magnetic fields are displayed.…”
mentioning
confidence: 99%
“…双金属富勒烯给荧光单分子磁体的 设计提供了很好的模板, 可以通过同时内嵌一个单分 子磁体性质优异的金属离子和一个具有发光性能的金 属离子到碳笼中来构造荧光单分子磁体. 2019年, 王春 儒和王太山研究组 [91] 合成分离了DyEr@C 82 的两个异 [40,41] DySc 2 N@D 5h -C 80 5.9 17.7±0.4 [41] Dy 2 ScN@D 5h -C 80 5.3 8.4±0.2 [41] DySc 2 N@D 3 (6140)-C 68 3.8 7.6±0.4 [41] Dy 2 ScN@C s (51365)-C 84 3.3 - [41] DyLu 2 N@I h -C 80 9.5 24.2±0.7 [42] Dy 2 LuN@I h -C 80 8.0 4.3±0.2 [42] DyErScN@I h -C 80 9.0 12.5 [43] HoSc 2 N@C 80 -16.5±0.6 [47] HoLu 2 N@C 80 -- [48] CCFs Dy 2 TiC@I h -C 80 2.0 - [32] Dy 2 TiC@D 5h -C 80 2.0 - [32] Dy [88] TbGd@I h -C 80 (CH 2 Ph) 14.4 - [88] TbY@I h -C 80 (CH 2 Ph) 5.0 - [88] Tb 2 @C 79 N 28.0 - [89] DyEr@C 3v (8)-C 82 <3.0 - [91] a) "-"表示文献中未给出相应数值. b~m) 表示同一物质在不同温度区间测得的数据经拟合得到的有效能垒(U eff )值, 对应的温度区间分别 为: b) 1.8~5 K; c) 63~76 K; d) 1.6~10 K; e) 15~35 K; f) 40~53 K; g) 1.6~4 K; h) 5~47 K; i) 47~70 K; j) 10~18 K; k) >20 K; l) 1.8~10 K; m) >10 K 构体DyEr@C s (6)-C 82 和DyEr@C 3v (8) [91] .…”
Section: Figureunclassified